Industry 4.0, servitization, and reshoring: A systematic literature review - Javier Bilbao-Ubillos; Vicente Camino-Beldarrain; Gurutze Intxaurburu-Clemente; Eva Velasco-Balmaseda (European Research on Management and Business Economics, 2024)
The goal of this literature review is first of all to help define, characterise and contextualise the phenomena that make up Industry 4.0 (I4.0), the servitisation of manufacturing and re-shoring; and secondly to explore the strong interactions between them. We conduct a systemic literature review to identify, synthesise, assess and interpret the findings of past studies to address the research question analysed here. Industry 4.0 technologies (I4.0Ts), and particularly increased digitisation, has made for the configuration of new business models and the servitisation of the economy in the context of a new paradigm of competition. This digital servitisation is conducive to networking and enhances the role of proximity. Together with other concurrent factors (changes in relative costs, agglomeration economies, the skills and expertise in data management required by I4.0Ts) this is favouring re-shoring. Technology is always present to a greater or lesser degree as an explanatory factor in re-shoring. The increasing cognitive complexity of technical solutions is enhancing proximity constraints. More frequent, more intense contacts are needed between customers and suppliers in a production set-up that is increasingly customised.